Analisis Struktur Puisi Rakyat Dalam Bentuk Mantra Pengobatan Di Desa Tegalsari Kecamatan Purwasari Kabupaten Karawang Serta Pemanfaatannya Sebagai Media Ajar Video Animasi Di SMP Kelas VII - Dewi, Lisnawati; Triadi, Slamet; Hartati, Dian (Peneliti.net, 2024)
Folk poetry, especially in the form of healing mantras, is rarely heard of. In the modern era, there are so many health workers, that the healing mantra is beginning to be eroded in certain areas. This is different from Tegalsari Village, Purwasari District, Karawang Regency, where some people still use healing spells due to several factors, namely economic factors, educational factors, and distant health development infrastructure factors. Apart from that, students can get to know folk poetry in the form of healing mantras, especially in Karawang Regency, using animated video teaching media. The research aims to analyze the structure of folk poetry in the form of healing mantras in Tegalsari Village, Purwasari District, Karawang Regency and its use as a teaching medium for animated videos in class VII junior high schools. The techniques used are observation, interviews, recording, notes and documentation. The research uses qualitative methods, namely describing the structure of folk poetry in the form of healing mantras. The researcher has several data on treatment spells from observations, namely: (1) spells for treating fever, (2) spells for treating scurvy, (3) spells for treating skin diseases, (4) spells for treating eye diseases, (5) spells for treating boils, (6) snake peck treatment spell. Apart from that, researchers utilized the research results as animated video teaching media.